2019
DOI: 10.12688/f1000research.18949.1
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of GRIN2A and GRIN2B variants in neurological conditions

Abstract: Rapid advances in sequencing technology have led to an explosive increase in the number of genetic variants identified in patients with neurological disease and have also enabled the assembly of a robust database of variants in healthy individuals. A surprising number of variants in the GRIN genes that encode N-methyl-D-aspartate (NMDA) glutamatergic receptor subunits have been found in patients with various neuropsychiatric disorders, including autism spectrum disorders, epilepsy, intellectual disability, att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 166 publications
(239 reference statements)
2
112
0
2
Order By: Relevance
“…Many genetic GRIN2A variants have been found in patients with epilepsy. The majority of these variants are located in the extracellular and transmembrane domains where they typically result in an overall increase in NMDAR-mediated currents 6,7 . However, a small number of mutations in the intrinsically disordered intracellular C-terminal domain have also been reported, including the missense variant on the GluN2A Ser-1459 phosphorylation site (S1459G) in an individual with focal epilepsy and speech disorder 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many genetic GRIN2A variants have been found in patients with epilepsy. The majority of these variants are located in the extracellular and transmembrane domains where they typically result in an overall increase in NMDAR-mediated currents 6,7 . However, a small number of mutations in the intrinsically disordered intracellular C-terminal domain have also been reported, including the missense variant on the GluN2A Ser-1459 phosphorylation site (S1459G) in an individual with focal epilepsy and speech disorder 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, NMDAR dysfunction has also been implicated in many human neurological disorders, including stroke, epilepsy, Alzheimer's disease, neuropathic pain and schizophrenia 5 . Moreover, genes that encode NMDAR subunits are remarkably intolerant to mutations, which have been associated with various human neurodevelopmental and neuropsychiatric disorders such as epilepsy, autism spectrum disorders, intellectual disability and schizophrenia 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, we found a twofold upregulation of GRIN2A and GRIN2B mRNA, which encode NMDAR subunit 2A and subunit 2B, respectively (Figure 4l-m). Aberrant expression of GRIN2A and GRIN2B has been shown to directly affect NMDA mediated current responses (49,50). To test whether the increased NMDAR subunit expression leads to increased NMDAR-mediated currents, control and missense Brunner syndrome DA neurons were stimulated with a local exogenous application of NMDA We found that the total current transfer mediated by the NMDA application was significantly increased in these neurons compared to controls (Figure 4o-p).…”
Section: Maoa Dysfunction Leads To Nmdar Hyperfunctionmentioning
confidence: 92%
“…In addition, 24 h treatment with 20 nM astaxanthin reduced the mRNA expression of other subunits (NR1, NR2A, NR2B); a temporary increase was observed after 4 h exposure [35]. Although NR2A and NR2B should share similar molecular structures and functions, they do in fact display a number of structural differences in receptors with various subunit compositions [36]. The NR2B subunit is highly expressed in the prenatal stages and its expression drops at the postnatal stages, becoming focally expressed in the forebrain; in contrast, NR2A is expressed at low levels in the prenatal stages and increases upon birth.…”
Section: Astaxanthinmentioning
confidence: 95%
“…The NR2B subunit is highly expressed in the prenatal stages and its expression drops at the postnatal stages, becoming focally expressed in the forebrain; in contrast, NR2A is expressed at low levels in the prenatal stages and increases upon birth. Additionally, variation in GRIN2A (the gene for the NR2A subunit) is commonly associated with an epileptic phenotype, while that in GRIN2B (the gene for the NR2B subunit) is commonly found in patients with neurodevelopmental disorders [36]. The distinct effect of astaxanthin on various NMDA receptor subunits may be significant in facilitating prolonged neuroprotection against high glutamate levels in people with neurological or psychiatric disorders.…”
Section: Astaxanthinmentioning
confidence: 99%